Simmel’s Philosophy of Money and Academic Specialization - S.M. Reza Amiri Tehranizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Philosophy of Money is the most important work of Georg Simmel that is ‎reconsidered nowadays in academies after that was neglected during the last century. ‎In contrast to its title, this book is not about economics. It is a book on ‎the multidisciplinary subject in the fields of philosophy, culture, psychology, social ‎sciences, and economics. This article has two goals; first, to introduce the content ‎of this work briefly and second, to analyze the relation of this book to academic ‎specialization in scientific disciplines. For the first purpose, the most important ‎concepts of the Philosophy of Money are reviewed briefly. The second purpose is ‎considered from two aspects; first, what are the reasons for reconsidering this work ‎in academies nowadays, after a century of neglect? And second, what relevance ‎can this work hold to the humanities and social sciences’ situation in Iran? Therefore, ‎in the first place, the Simmel’s theory of social forms is reviewed, and then upon ‎it, concepts such as objectification, ramification, subject-object, modernity, ‎aesthetics, end-mean, and the form of religion are discussed. In appraising the ‎relevance of Philosophy of Money to academic specialization in the contemporary ‎world and especially to the academic atmosphere in Iran, nowadays phenomena of ‎the booming of interdisciplinary research in humanities and social sciences and ‎the relation of religion to these sciences are considered.‎